DAMPAK PEMEKARAN WILAYAH KABUPATEN KAYONG UTARA TERHADAP PENERIMAAN DAN PENGELUARAN KABUPATEN KETAPANG - B61110058, M. RASYID REDHA (Jurnal Ekonomi Daerah (JEDA), 2014)
ABSTRACT This study aims to analyze the proportion and growth of each component of revenues over total revenues in Ketapang district budget before and after the splitting of the region , analyzing the proportion and growth of each component of indirect expenditures and direct expenditures to total expenditures indirect and direct expenditures in the budget before and after the splitting of the region , as well as analyze the efficiency and effectiveness of financial management district ketapang before and after the expansion area . The analysis of the data used by the analysis tool Comparative Budget Statement ( CBS ) . CBS Horizontal , used to see the development of each component of indirect revenues and expenditures are absolute , relative and ratios . Vertical CBS then used to look at the proportion of each component in the receipt and expenditure of each component is not directly in percentages . The use of the analysis tool is intended to determine the impact of the expansion of the receipts and expenditures of the period before and after the expansion of the division . The analysis showed that the average growth in earnings before splitting of the proportion of 28.26 % with an average of 12.36 and an average expansion after growth amounted to 4320.34 % and the average proportion of 12.12 . Average spending growth is not directly before the expansion area of 22.33 with an average proportion of 16.67 , while the average expansion after growth increased to 30.29 % with the average proportion fixed at 16.67 % . Average spending growth immediately before the division of 45.18 % with an average proportion of 36.39 % and an average expansion after growth slowed to 0.97 % with an average proportion of 33.33 % . The results of an analysis of the financial management area that is obtained before and after the division of the region into the category quite efficient and effective . The password : Earnings, Indirect Expenditures, direct Expenditure